CANDIDATE LABORATORY MARKERS OF LONG-TERM FUNCTIONING OF THE DUCTUS ARTERIOSUS IN EXTREMELY LOW BIRTH WEIGHT INFANTS - Мария Вячеславовна Пересторонина; Сергей Владимирович Пальянов; Ольга Валентиновна Корпачева (Медицина в Кузбассе)
Objective. Pathogenetic relationships between clinical, biochemical blood parameters and long-term functioning of the patent ductus arteriosus (PDA) in newborns with extremely low birth weight (ELBW).